China and the South: Objectives, Actors and Interactions. Issue 6 (4th November 2013) - Breslin, Shaun
ABSTRACT: China has stepped up its engagement of developing countries through both bilateral interactions and the establishment of more formal multilateral fora. To achieve this, China's leaders have established a clear state policy designed to secure much needed resources and to establish an identity as a new and different type of 'great power'. China has also become a proactive provider of development aid which, when combined with other forms of economic engagement, have raised concerns in the West that China is undermining the promotion of a liberal global order. But we need to take care in considering who, or what, is driving Chinese policy. The institutional weakness of the Ministry of Foreign Affairs means that commercial and financial agencies have dominated the agenda; major state owned enterprises and increasingly large numbers of small, often private enterprises are pursuing their own commercial agendas overseas, which are often not controlled by Beijing. The result is a patchwork of different types of relationships with developing countries, more often driven by the commercial concerns of economic actors than by a coherent diplomatic strategy.